The Role of Islamic Religious Education Teachers and Parents in the Formation of Student Morals After the COVID-19 Pandemic at Muhammadiyah Plus Salatiga Junior High School in 2023 - Azizah Azizah (Transpublika Publisher, 2026)
The COVID-19 pandemic brought significant changes to students’ learning environments and social interactions, creating new challenges for moral development. This study aims to examine the role of Islamic Religious Education (PAI) teachers and parents in shaping students’ morals after the COVID-19 pandemic at Muhammadiyah Plus Salatiga Junior High School in 2023. This study employed a descriptive qualitative field research design. The subjects were PAI teachers and parents of students at Muhammadiyah Plus Salatiga Junior High School. Data were collected through in-depth interviews and observations, while data analysis consisted of data reduction, data presentation, and conclusion drawing. The findings revealed that PAI teachers contributed to students’ moral formation by acting as organizers, correctors, motivators, and facilitators. Parents supported moral development by helping students establish positive habits, providing role models, and supervising activities related to moral values. The moral formation process was supported by teacher competence, a conducive school environment, a supportive curriculum and learning materials, and active parental involvement. However, several factors hindered this process, including negative environmental influences, the uncontrolled use of technology and social media, limited parental involvement, family conflicts, lack of parental attention, and inadequate understanding of religious and moral values. The study highlights the importance of collaboration between schools and families in fostering students’ moral development in the post-pandemic era.